2022
DOI: 10.1177/10711007221126736
|View full text |Cite
|
Sign up to set email alerts
|

The Foot and Ankle Kinematics of a Simulated Progressive Collapsing Foot Deformity During Stance Phase: A Cadaveric Study

Abstract: Background: Progressive collapsing foot deformity (PCFD) is a complex pathology associated with tendon insufficiency, ligamentous failure, joint malalignment, and aberrant plantar force distribution. Existing knowledge of PCFD consists of static measurements, which provide information about structure but little about foot and ankle kinematics during gait. A model of PCFD was simulated in cadavers (sPCFD) to quantify the difference in joint kinematics and plantar pressure between the intact and sPCFD conditions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(27 citation statements)
references
References 56 publications
0
27
0
Order By: Relevance
“…A recent robotic cadaveric gait study by Henry et al 15 demonstrated this aberrant talar internal rotation in their simulated PCFD model. Although they confirmed the 3D talar motion within the mortise in PCFD, the authors did not provide an explanation for the aberrant internal rotation of the talus.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…A recent robotic cadaveric gait study by Henry et al 15 demonstrated this aberrant talar internal rotation in their simulated PCFD model. Although they confirmed the 3D talar motion within the mortise in PCFD, the authors did not provide an explanation for the aberrant internal rotation of the talus.…”
Section: Discussionmentioning
confidence: 93%
“…24 PCFD has been described as a 3-dimensional (3D) deformity centered around the talus, with eversion of the subtalar joint, lateral/dorsal translation of the navicular, and collapse of the medial longitudinal arch. 15,21,32 The motion of the talus itself in the mortise also has been described, such as narrowing of the posterior tibiotalar joint from talar sagging in the sagittal plane or valgus talar tilt in the coronal plane, 1,7,16,18 implying that multiplanar motion of the talus also occurs at the tibiotalar joint.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Future research should be aimed at incorporating robotic technologies into both surgical procedure and clinical practice, and assessing the impact on both implant position (particularly femoral component rotation) and patient outcome 114,115 . Ultimately, less-invasive, bone and soft tissue-sparing techniques will serve to benefit the patient, but only after they are vetted by extensive research and clinical practice.…”
Section: Resultsmentioning
confidence: 99%
“…3,12,13,22 A tear of the spring ligament results in abduction deformity at the TN joint, which increases the stress on the tendons and ligaments of the medial foot which then leads to further foot collapse. 19,22 Recent cadaveric studies have demonstrated that the spring ligament maintains medial tibiotalar stability by forming a large confluent ligament (tibiospring ligament) with the superficial deltoid ligament, 7,11 highlighting its crucial role in preventing the peritalar instability observed in PCFD.…”
Section: Introductionmentioning
confidence: 99%